Self-service AI with Power BI Desktop machine learning insights for business - Ehrenmueller-Jensen, Markus (Apress L.P., 2020)
This book explains how you can enrich the data you have loaded into Power BI Desktop by accessing a suite of Artificial Intelligence (AI) features. These AI features are built into Power BI Desktop and help you to gain new insights from existing data. Some of the features are automated and are available to you at the click of a button or through writing Data Analysis Expressions (DAX). Other features are available through writing code in either the R, Python, or M languages. This book opens up the entire suite of AI features to you with clear examples showing when they are best applied and how to invoke them on your own datasets. No matter if you are a business user, analyst, or data scientist - Power BI has AI capabilities tailored to you. This book helps you learn what types of insights Power BI is capable of delivering automatically. You will learn how to integrate and leverage the use of the R and Python languages for statistics, how to integrate with Cognitive Services and Azure Machine Learning Services when loading data, how to explore your data by asking questions in plain English ... and more! There are AI features for discovering your data, characterizing unexplored datasets, and building what-if scenarios. Theres much to like and learn from this book whether you are a newcomer to Power BI or a seasoned user. Power BI Desktop is a freely available tool for visualization and analysis. This book helps you to get the most from that tool by exploiting some of its latest and most advanced features. You will: Ask questions in natural language and get answers from your data Let Power BI explain why a certain data point differs from the rest Have Power BI show key influencers over categories of data Access artificial intelligence features available in the Azure cloud Walk the same drill down path in different parts of your hierarchy Load visualizations to add smartness to your reports Simulate changes in data and immediately see the consequences Know your dat a, even before you build your first report Create new columns by giving examples of the data that you need Transform and visualize your data with the help of R and Python scripts.
R Script Visual: Scatter with Spline. - Includes bibliographical references and index. - Print version record
Keywords: Microsoft .NET Framework; Business -- Data processing; Artificial intelligence; Machine learning; Computer science; Artificial Intelligence; Electronic Data Processing; Machine Learning; Gestion; Informatique; Intelligence artificielle; Apprentissage automatique; Informatique; artificial intelligence; Microsoft programming; Computers; Intelligence (AI) & Semantics; Computers; Computer Science; Computers; Programming; Microsoft Programming; Business; Data processing